Status Gizi dan Sarkopenia pada Pasien Penyakit Hati Berlemak Non-Alkohol di sebuah Rumah Sakit Swasta di Coimbatore, India: Nutritional Status and Sarcopenia in Patients with Non-Alcoholic Fatty Liver Disease at a Private Hospital in Coimbatore, India - Afshan, Kamar; Dhandapani, Shanthi; Kuppusamy, Balu; Swaminathan, Mukundhan; Farapti, Farapti (Amerta Nutrition, 2025)
Background: The Global prevalence of sarcopenia was estimated as 10% to 27% among Non-Alcoholic Fatty Liver Disease (NAFLD) patients. Objectives: To investigate the association between nutritional status and sarcopenia among NAFLD patients. Methods: The study was conducted between January 2024 and June 2024 and included 218 study participants. The social and demographic profile, dietary habits, fatigue, and 24-hour recall dietary intake were assessed using the interview cum questionnaire. Bio Impendence Analysis (BIA) and a hand grip dynamometer were used to assess the MM and MS. Functional capacity was analysed using the 6-Minute Walk Test (6MWT). Results: The relationship between relative risk factors and sarcopenia showed that male had a Relative Risk Ratio (RRR)=4.048 (95% CI: 1.073-15.275), overweight RRR=5.929 (95% CI: 1.42-24.763), Muscle Mass (MM) RRR=0.857 (95% CI: 0.741-0.99), Muscle Strength (MS) RRR=0.809 (95% CI: 0.729-0.898), Neutrophil-to-Lymphocyte Ratio (NLR) RRR=0.254 (95% CI: 0.069-0.933), moderate fatigue RRR=0.313 (95% CI: 0.107-0.921), 6MWT RRR=0.989 (95% CI: 0.981-0.996). Conclusions: A reduction in MM, MS, and physical performance had shown a significant association with sarcopenia, indicating the reduction in these factors can lead to an increase in sarcopenia. Tailoring the intervention to increase the MM, strength, and physical performance can help in reducing the progression of  sarcopenia and disease outcomes.